Comparison of Thermoelastic Results in Two Types of Functionally Graded Brake Discs - B.B, Sahari (Universiti Malaysia Pahang, 2012)

(untitled)
A thermoelastic simulation of functionally graded (FG) brake discs is performed using finite element (FE) ANSYS. The material properties of two types of FG brake discs are assumed to vary in both radial and thickness directions according to a power law distribution. The brake discs are in contact with one hollow pure pad disc. Dry contact friction is considered as the heat source. The proper thicknesses of pad discs are found to have full-contact status. The behaviour of the thermoelastic results for thickness and radial FG brake discs are compared. The results show that the behaviour of temperature and vertical displacement in these two types of FG brake discs are the same. However, the variations of radial displacement for different grading indices n are not the same. The behaviour of other results are quite similar. Thus, it can be concluded that the variation direction of material properties in FG brake discs can affect the results.